Intriguing role of novel ionic liquids in stochastic degradation of chitosan. (15th May 2021) - Pandit, A.; Khare, L.; Ganatra, P.; Jain, R.; Dandekar, P.
Graphical abstract: Highlights: Synthesis of novel Brønsted Acidic Ionic Liquids via a microwave mediated process. ILs degraded chitosan into its low molecular weight variants. Box Behnken design revealed the process parameters important for chitosan degradation. BAILs permitted controlled degradation of chitosan. Abstract: Green technique for hydrolysis of chitosan was developed using novel Brønsted Acidic Ionic Liquids (BAILs) as homogenous reusable catalysts. Efficiency of BAILs in controlling stochastic and irregular breakdown of chitosan was compared with that of mineral acids. Structural elucidation of the novel BAILs was performed using H 1 -NMR evaluation and supplemented using mass spectroscopy. Additionally, thermal characterization was conducted using TGA-DTA analysis, while acidity was estimated by deriving the Hammet acidity function. BAILs investigated in this work enabled consistent production of LMWCS variants, with minimum formation of residual impurities. Around 80 % reduction in molecular weight was noted as compared to original under extreme conditions employed. Further, Box-Behnken Design (BBD) was implemented to optimize effect of processing parameters for conversion of chitosan to low molecular weight congeners.